APLIKASI MULSA PLASTIK DAN PUPUK KOMPOS PADA PERTANAMAN WORTEL DI KECAMATAN TOMOHON TIMUR KOTA TOMOHON - Kamagi, Y. E. B.; Supit, Joice M. J.; Kaunang, Djoni (EUGENIA, 2019)
Research conducted in the field aims to obtain data and information about: 1). Organic carrot products; 2). The best combination of treatments for carrot production; and 3). Some physical properties of the soil are a result of treatment. Â The things observed include the main data, namely: bulk density, moisture content, soil permeability and production of carrots and additional data, namely: organic C, N, P, K. and pH in soil and compost, soil texture, rainfall, temperature and altitude. Â The research method is a 2-factor randomized block design with 3 replications. The first treatment is plastic mulch with two levels of treatment, namely: 1). Plants with plastic mulch (0) and 2). Plants without plastic mulch (1). The second treatment is compost with three levels of doses, namely: 1). 0 tons/ha; 2). 15 tons/ha; and 3). 30 tons/ha. The results showed that the use of plastic mulch and compost 15 tons/ha gave higher production, which was 2.93 kg perplot.